Sistem gadaian Islam - Asmadi Mohamed Naim, (Penerbit Universiti Kebangsaan Malaysia, 2004)
This article seeks to analyze and compare between the traditional pawning transactions and Islamic pawning transactions practiced in Malaysia as seen from the Islamic perspective. The analysis is qualitative in its approach, the usual approach normally adopted by most Islamic scholars. The article begins with the discussion of the rules and procedures governing the Islamic mortgage system, followed by comparative analysis of the two systems against the rules and theories as prescribed by the Islamic law. The article concludes that many of the Islamic law, whilst some practices adopted by the Islamic system are “not truly in compliance” with the teaching of the Islamic law